PARTISIPASI LEMBAGA PEMBERDAYAAN MASYARAKAT DESA DALAM MELAKSANAKAN PEMBANGUNAN DESA SEBAGAI PERWUJUDAN CIVIC PARTICIPATORY DI DESA BLORONG KECAMATAN JUMANTONO KABUPATEN KARANGANYAR - Hastuti, Dwi; ., Rusnaini; Yuliandari, Erna (PKn Progresif, 2017)
ABSTRACTThe objective of research was to find out: (1) the participation of Village Community Empowerment Institution in implementing Village Development as the Manifestation of Civic Participatory in Blorong Village, Jumantono Sub District and Karanganyar Regency and (2) the factors affecting the participation of Village Community Empowerment Institution in implementing Village Development as the Manifestation of Civic Participatory in Blorong Village, Jumantono Sub District and Karanganyar Regency. This research employed qualitative method with a single embedded case study approach. The data source was obtained from informant, place and event, and documentation. The sampling technique used was purposive sampling. Techniques of collecting data used were interview, observation, and document analysis. Data validation was conducted using data and method triangulations. Meanwhile, technique of analyzing data used was an interactive model of analysis encompassing: (1) Data collection, (2) data reduction, (3) data display, and (4) conclusion drawing. The procedure of research included: (1) preparation, (2) data collection, (3) data analysis, and (4) research report writing. Considering the result of research, the following conclusion could be drawn. (1) The participation of Village Community Empowerment Institution in implementing Village Development as the Manifestation of Civic Participatory in Blorong Village is not optimal. It could be seen from its participation in each of stages in the development of Blorong Village from planning, implementation, development and utilization of development results. (2) The participation of Village Community Empowerment Institution in implementing development was affected by factors included: first, allowances for members of LPMD. Second,regulation of LPMD. Third, support from society. Fourth, stranded good communication between LPMD and society. Meanwhile, inhibiting factors included: first, gradual fund issuance. Second, low awareness of LPMD. Third, low trust society to village goverment showed with society?s prejudice and dissenting opinion. Fourth, as well as the lack of openness Village Government. Keywords: Participation, Village Community Empowerment Institution, Village Development, Civic Participatory